2020
DOI: 10.1186/s12978-020-0901-8
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol administered sublingually at a dose of 12.5 μg versus vaginally at a dose of 25 μg for the induction of full-term labor: a randomized controlled trial

Abstract: Background: Labor induction is defined as any procedure that stimulates uterine contractions before labor begins spontaneously. The vaginal and oral routes of administration of misoprostol are those most used for the induction of labor in routine practice, with the recommended dose being 25 μg. Nevertheless, the sublingual route may reduce the number of vaginal examinations required, increasing patient comfort and lowering the risk of maternal and fetal infection. Based on a previous systematic review, the obj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is also possible to display intracervical and sublingual administration as a more effective route than vaginal agents. Gattás's study_ A randomized, placebo-controlled trial of 12.5 µg sublingual and 25 µg vaginal dose administration found that in the sublingual community, the duration between the rst dose of misoprostol and the onset of labor was shorter (26). Sublingual misoprostol was also found in the Ayati's study to be as successful as vaginal misoprostol for term labor induction.…”
Section: Discussionmentioning
confidence: 97%
“…It is also possible to display intracervical and sublingual administration as a more effective route than vaginal agents. Gattás's study_ A randomized, placebo-controlled trial of 12.5 µg sublingual and 25 µg vaginal dose administration found that in the sublingual community, the duration between the rst dose of misoprostol and the onset of labor was shorter (26). Sublingual misoprostol was also found in the Ayati's study to be as successful as vaginal misoprostol for term labor induction.…”
Section: Discussionmentioning
confidence: 97%
“…These data are consistent with previous studies. According to these studies, patients receiving a vaginal insert with Misoprostol more often required intrapartum analgesia with opioids [ 25 , 26 , 27 ]. However, due to the study design, these figures may be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to display intracervical and sublingual administration as a more effective route than vaginal agents. Gattás’s study_ A randomized, placebo-controlled trial of 12.5μgm sublingual and 25μgm vaginal dose administration found that in the sublingual community, the duration between the first dose of misoprostol and the onset of labor was shorter [ 24 ]. Sublingual misoprostol was also found in Ayati’s study to be as successful as vaginal misoprostol for term labor induction.…”
Section: Discussionmentioning
confidence: 99%